Antihypertensive Therapy, Blood Pressure Variability, and Dementia Risk in Asian Populations: A Systematic Review and Meta-Analysis - sepridawati siregar; Nora Idiawati; Larysa Fernenda; Yessi Rahayu; Muchsin Maulana (LPPM Universitas Abdurrab, 2026)
Hypertension and blood pressure variability (BPV) are recognized as modifiable risk factors for dementia, yet evidence in Asian populations remains limited. This study systematically evaluated the association between antihypertensive therapy, BPV, and dementia risk in Asia. A systematic search of ScienceDirect, PubMed, and MEDLINE (2010–2024) was conducted following PRISMA guidelines. Studies reporting hazard ratios (HRs) for dementia outcomes in Asian populations were included. Of 1,246 identified records, 22 studies met criteria for qualitative synthesis and 15 were included in the meta-analysis (11 cohort, 4 case-control). Antihypertensive therapy was associated with reduced dementia risk (pooled HR ≈ 0.84), while high BPV was linked to increased risk (pooled HR ≈ 1.23). Meta-regression identified study design and mean age as sources of heterogeneity. Overall, antihypertensive therapy appears protective, whereas elevated BPV increases dementia risk in Asian populations, emphasizing the importance of both blood pressure control and stability in preventing cognitive decline.